Analisis Jenis, Jumlah dan Mutu Sarapan Pagi Siswa Sekolah Dasar - Sopiyandi Sopiyandi; Widyana Lakshmi Puspita (Jurnal Vokasi Kesehatan, 2016)
Abstract: Type Analysis, Number and Quality Breakfast of Children on Elementary School. The research objective is to analyze the full breakfast at the elementary school students in District Rasau Jaya covering aspects of the type, quantity and quality of the breakfast. This research is an analytic with Cross sectional study design. Subjects were students at SDN 1 Rasau Jaya aged 8-12 years, a large sample of 215 respondents. The results showed that as many as 98.6% of students breakfasts with ten types of food most consumed by children during breakfast ie eggs, white rice, fried rice, yellow rice, tempeh, bulb meatballs, dumplings, bread, sausages and porridge. While the five types of beverage most consumed by children during breakfast was tea, milk, juice, water, and syrup. 54% of the number of good energy, 51% protein and 68.4% fat in both categories. 61.9% carbohydrate intake is not good. The nutritional quality of food is quite good kid.Abstrak : Analisis Jenis, Jumlah Dan Mutu Sarapan Pagi Siswa Sekolah Dasar. Tujuan penelitian yaitu untuk menganalisis sarapan pagi pada siswa Sekolah Dasar di Kecamatan Rasau Jaya meliputi aspek jenis, jumlah dan mutu sarapan. Penelitian ini bersifat analitik dengan desain penelitian Cross sectional. Subjek penelitian adalah siswa SDN 1 Rasau Jaya usia 8-12 tahun, besar sampel penelitian sebanyak 215 responden. Hasil penelitian menunjukkan bahwa sebanyak 98,6 % siswa sarapan dengan sepuluh jenis makanan yang paling banyak dikonsumsi oleh anak selama sarapan yaitu telur ayam, nasi putih, nasi goreng, nasi kuning, tempe, pentol bakso, siomay, roti, sosis, dan bubur. Sedangkan lima jenis minuman yang paling banyak dikonsumsi oleh anak selama sarapan adalah teh, susu, air jeruk, air putih, dan sirup. Sebanyak 54% jumlah energi baik, protein 51 % dan lemak 68,4% pada kategori baik. 61,9% asupan karbohidrat tidak baik. Mutu gizi pangan anak tergolong baik.